(untitled) (Research, Society and Development, 2023)
This is a descriptive study of the experience report type, which aims to report the playful strategies developed by the project "Oral Health Care for School Children and the Community" of the State University of Londrina to promote oral health in extension actions that took place in Early Childhood Education Centers and municipal schools. For this, in an initial moment, the students were divided into groups and chose the ludic resources to be carried out. Subsequently, each group was responsible for presenting the playful strategy for approval and suggestions from all participants. The ludic strategies developed were: use of fantasies of the tooth fairy, tooth and caries bug; puppet theater and/or with actors; educational games and songs. During the execution of the strategies, it can be noticed that the children were happy, stimulated and more receptive to the presence of the students and participatory in the activities. For the students, associating sensitive health issues with the ludic in extension actions represented opportunities for student qualification supported by ethical, loving and empathetic pillars. In addition, playful strategies relate to powerful welcoming and humanized approach tools that promote quality of life for children.